1984
DOI: 10.1128/jcm.20.6.1099-1101.1984
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Syrian hamsters with Lyme disease spirochetes

Abstract: Syrian hamsters were shown to be susceptible to infection by the Lyme disease spirochete Borrelia burgdorferi. Although these spirochetes did not cause any outward signs of illness in these animals, they did cause a generalized infection. Spirochetemia was present during the first 6 days of infection. At 14 days postinfection, spirochetes could be isolated from one or more of the following organs: spleen, eyes, kidneys, liver, testes, and brain. Spirochetes were isolated from the eyes and kidneys of one animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(98 citation statements)
references
References 10 publications
4
93
1
Order By: Relevance
“…In early studies of this organism, it was determined that its genome consisted of a linear chromosome and multiple linear and circular plasmids ranging in size from 56 kbp to 5 kbp. Many of these plasmids were easily lost during in vitro culture, and absence of some of these plasmids correlated with loss of infectivity in animal models (15)(16)(17)(18)(19)(20)(21)(22)(23). The availability of the genome sequence of B. burgdorferi B31 showed that the organism contained 12 linear and 9 circular plasmids (with a total of over 600 kbp) as well as a 972 kbp linear chromosome (24,25).…”
Section: Vls System Of B Burgdorferi B31mentioning
confidence: 99%
“…In early studies of this organism, it was determined that its genome consisted of a linear chromosome and multiple linear and circular plasmids ranging in size from 56 kbp to 5 kbp. Many of these plasmids were easily lost during in vitro culture, and absence of some of these plasmids correlated with loss of infectivity in animal models (15)(16)(17)(18)(19)(20)(21)(22)(23). The availability of the genome sequence of B. burgdorferi B31 showed that the organism contained 12 linear and 9 circular plasmids (with a total of over 600 kbp) as well as a 972 kbp linear chromosome (24,25).…”
Section: Vls System Of B Burgdorferi B31mentioning
confidence: 99%
“…Sera were collected one week later, and the development of antibody against the corresponding borrelial antigen was confirmed by ELISA and immunoblot analysis (not shown). Each group of hamsters was then challenged with a single intraperitoneal injection of B. burgdor-feri (10 8 cells/animal), as previously described [30]. Twelve days post challenge, the hamsters were sacrificed and spirochete levels were measured in the joint, heart and bladder samples by quantitative PCR.…”
Section: Immunization Of Hamsters With Ndv-vectored Bmpa Interferes Wmentioning
confidence: 99%
“…Signs of arthritis and carditis become apparent at 2-3 weeks and then resolve after 7-8 weeks although mice remain infected for months. Similar to mice, hamsters of both sexes and all ages are susceptible to disseminated infection [30,31]. The use of hamsters as a rodent model of Lyme borreliosis gained immediate attention following discovery of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Lyme disease spirochetes grow only in extremely rich, undefined medium, and take one to several weeks to form a visible colony (Barbour, 1984;Elias et al ., 2002). In addition, in vitro culture is associated with variable loss of plasmids and a concomitant loss of infectivity (Johnson et al ., 1984;Barbour, 1988;Simpson et al ., 1990;Norris et al ., 1995;Purser and Norris, 2000;Labandeira-Rey and Skare, 2001). In part because of the problematic nature of in vitro culture, genetic manipulation of these bacteria has been difficult, and genetic approaches similar to those used to study most other bacterial pathogens have not been possible for Lyme disease spirochetes, much to the frustration of investigators in the field.…”
Section: Lyme Disease and The Biology Of Borrelia Burgdorferimentioning
confidence: 99%